THE DICTATORSHIP OF THE PARTISAN - Gailius, Bernardas (Politologija, 2015)
If the guerrilla war is interpreted according to the concept of Carl Schmitt, its relation to the political nation becomes apparent. It takes little effort to see in “the defensive-autochthonous defender of home” the modern citizen par excelence – the one who is ready to take up arms in defense of his fatherland. However this interconnection escaped the attention of C. Schmitt himself. Therefore “The Theory of Partisan” was left independent of the C. Schmitt’s concept of the sovereignty (“Sovereign is he who decides on the exception”). But if the guerrilla war is considered as itself the state of exception, it opens the way for the qualitatively new theory.The most visible and practical appearance of the European national sovereignty was the revised concept of the citizenship. It became some kind of political kinship. The state (political nation) guaranteed the rights of the citizen, but on the other hand the mere existence of the state itself depended of the patriotic stance of the citizen. The only known earlier model of such political community was the ancient republic of Rome. Therefore quite unsurprisingly the new European nomos of the 19th and the 20th centuries had many Roman features.The Roman precedent of the guerrilla war was known as iustitium – the ancient concept of the state of exception, recently revised and reconsidered by Giorgio Agamben. Although it could acquire different military forms, politically it always meant the same phenomenon – the direct exercise of the governmental power (imperium) by the ordinary citizens. In turbulent times they were empowered to take any steps necessary for the salvation of the republic. The same practical enactment of the national sovereignty forms the essence of the modern guerrilla war.However, the partisan is not only the “autochthonous defender”, but also a political figure. In modern times (as opposed to the ancient Rome) he does not identify with the established political order. The historical analysis provides that the partisan of the 19th and the 20th centuries not only defended his homeland, but also sought the renewal of the political regime. Therefore he embodied the creative as well as the conservative aspect of the sovereign power belonging to the political nation.This conclusion leads to the problem of evaluating the transitional political order that evolves during the guerrilla war. The C. Schmitt’s concept of the sovereign dictatorship seems to answer the question. Being the sovereign dictators the partisans act as if they were actual sovereigns – they do not consider themselves bounded by any previous law. On the other hand as the representatives of the political nation they are only empowered to seek the objectives compatible with the general will of that nation.